2011
DOI: 10.1002/adma.201101042
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically Porous TiO2 Electrodes Fabricated by Dual Templating Methods for Dye‐Sensitized Solar Cells

Abstract: Dual templating methods to control hierarchical meso‐ and macroscale pores in TiO2 electrodes for dye‐sensitized solar cells are developed. The colloidal assembly of mesoscale particles in holographic lithography macroscopic patterns produces dual templates for hierarchically porous electrodes. The hierarchical TiO2 electrodes show synergistic effects of strong scattering and long charge recombination times, resulting in an efficiency comparable to the efficiency of conventional TiO2 electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 21 publications
1
91
0
Order By: Relevance
“…4,82 Additionally, the porous materials of an inverse opal can be backfilled by smaller colloidal particles ( Figure 4B,iii), producing more complex materials with higher porosity and choice of materials. 88,140 (iv) Crack formation and homogeneity. The formation of cracks is generally unwanted and results from various origins.…”
Section: (D) Multiple Porositiesmentioning
confidence: 99%
“…4,82 Additionally, the porous materials of an inverse opal can be backfilled by smaller colloidal particles ( Figure 4B,iii), producing more complex materials with higher porosity and choice of materials. 88,140 (iv) Crack formation and homogeneity. The formation of cracks is generally unwanted and results from various origins.…”
Section: (D) Multiple Porositiesmentioning
confidence: 99%
“…C. Y. Cho et al reported an interesting method to generate hierarchical electrodes consisting of meso-and macroscale pores (Cho et al, 2011). Mesoscale colloidal particles and lithographically patterned macropores were used as the dual templates, with the colloidal particles assembled within the macropores.…”
Section: Hierarchical Photoanodesmentioning
confidence: 99%
“…Four-beam interference is one of the interference techniques used for the fabrication of large-area functional structures due to its outstanding capability in one-step realization of 2D/3D structures [15,16,18,[25][26][27][28]. As shown in Fig.…”
Section: Fabrication Of Functional Structures By Four-beam Interferencementioning
confidence: 99%
“…The flexible tuning of beam angle widens the period from microscale to nanoscale and promotes its widespread applications in surface science [5]. With the detailed multibeam interference and multi-exposure of two-beam interference, structures such as microlenses [10], photonic quasi-lattices [24], and micro/nanopillars (micro/nanoholes) [18,25], and several micro/nanostructures based on these templates [11,16] are easily demonstrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation